1993
DOI: 10.1073/pnas.90.14.6864
|View full text |Cite
|
Sign up to set email alerts
|

Intervening sequence with conserved open reading frame in eubacterial 23S rRNA genes.

Abstract: An intervening sequence (IVS) occurred in the 23S rRNA genes (rrl) of some, but not all, strains of four species of the spirochete genus Leptospira and was absent from strains in three other species. The IVS varied in size from 485 to 759 base pairs and replaced bases 1224-1245 in both copies of rrl. The two ends of each IVS shared 22-35 bases of complementarity that could form a stable double helix. The presence of an IVS correlated with a cleaved mature 23S rRNA that probably results from removal of the IVS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 25 publications
(44 reference statements)
3
52
0
1
Order By: Relevance
“…Intervening sequences, in contrast to introns, cannot self-splice from precursor RNA and, upon removal by cellular maturation enzymes, leave the ribosomal RNA fragmented (3)(4)(5)(6)(7). In this study, we also showed that true selfsplicing introns can be present in bacterial 16S rRNA genes, leading to the conclusion that the 16S rRNA genes of bacteria can indeed be far longer than ∼1,500 nucleotides.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Intervening sequences, in contrast to introns, cannot self-splice from precursor RNA and, upon removal by cellular maturation enzymes, leave the ribosomal RNA fragmented (3)(4)(5)(6)(7). In this study, we also showed that true selfsplicing introns can be present in bacterial 16S rRNA genes, leading to the conclusion that the 16S rRNA genes of bacteria can indeed be far longer than ∼1,500 nucleotides.…”
Section: Discussionsupporting
confidence: 53%
“…The possibility that the 16S rRNA gene may not have a conserved size has not been sufficiently considered in designing and applying techniques for diversity studies, even though elongations of 16S rRNA genes due to intervening sequences have been reported before (3)(4)(5)(6)(7). Intervening sequences, in contrast to introns, cannot self-splice from precursor RNA and, upon removal by cellular maturation enzymes, leave the ribosomal RNA fragmented (3)(4)(5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 3A). Similar sequence blocks have been shown to be present at this position in the 23S rRNA genes from a variety of bacteria (3,20,44,47,52,60) and chloroplasts (59), and these extra sequence blocks in the 23S rRNA genes have been termed intervening sequences (3) or transcribed spacers (60).…”
Section: Resultsmentioning
confidence: 85%
“…The presence of IVSs resulting in such 23S rRNA fragmentation was first described for Salmonella enterica serovars Typhimurium and Arizonae (5), for which it was shown that the IVS was excised posttranscriptionally by endoribonuclease RNase III without religation (5). IVSs have been identified in and characterized for other bacteria, including Yersinia enterocolitica (37), Coxiella burnetii (2), Helicobacter (18), and Haemophilus (39), Brucella (4), Leptospira (35), Proteus, and Providencia (27) spp. Horizontal gene transfer has been postulated to underlie the dissemination of IVSs (34,36).…”
mentioning
confidence: 99%